Dream and Bade Motif in the Process of Transition to Ashik: Ashik Mah Turna from Diyarbakır - Yalçınkaya, Fatoş (Journal of Alevism-Bektashism Studies, 2022)
The Southeastern Anatolia Region has been an area where many Alevi ocaks have existed from past to present days. Many ocaks have been found in Diyarbakir, which is located in this region. Diyarbakir is the place where ocaks have been actively preforming their rituals for many years. The Diyarbakir ocaks, where cem rituals were actively performed until recently, caused many talips (followers) to come here at certain times and even some to settle here. Today, the case is different. The Alevi community in Diyarbakir has diminished considerably and it has become impossible to preform cem rituals. Many zakirs and ashiks were raised in Diyarbakir, which has a rich Alevi culture. With reference to the poems of Mah Turna, an Alevi ashik from Diyarbakir, our paper analyses her place and importance in the ashik tradition. The base of our paper is the fact that Mah Turna is a female ashik. Considering that until recently female ashiks have not been researched much, we hope that this paper will contribute, even a little, to the field. In recent years, it is seen that more studies on female ashiks have been carried out. In the past, female ashiks were mostly ignored during collecting information from sources. Female performers were consulted only when no other source was found. Today’s studies have shown that there is a lot of female ashiks. Accordingly, we found it useful to discuss and analyse a female ashik as a support to such studies.Mah Turna is an important performer and carrier of the Alevi ashik tradition. Mah Turna, who reached the rank of ashik by drinking bade from the hand of the Prophet Muhammad in her dream, is in the group of badeli ashiks in the ashik tradition. Mah Turna, who grew up in the Alevi tradition and participated in the cems and Yas-i Muharem rituals, is the living witness and performer of the tradition. The beliefs of the Alevi community, which member she is, left their mark on Mah Turna’s identity as an ashik. All the negative experience that female ashiks had, Mah Turna, albeit partially, also had it. But she continued the ashik tradition by bearing the brunt of many difficulties. She learned to create poetry with syllabic verse from ashik Niyazi, to play the divan saz from zakir Bektash Akbay, and the choghur from zakir Hanifi Atabay. Mah Turna is a badeli ashik who was instructed in the master-apprentice learning model. The information about MahTurna’s life and poems are taken from Bulent Akin’s work titled Diyarbakırlı Bir Halk Şairi Âşık Mah Turna (Ashik Mah Turna a Folk Poet from Diyarbakir).
Keywords: Alevi; female ashik; ashik Mah Turna; dream; bade